Predictive value of peripheral blood SNORD55 for prognosis of atrial fibrillation patients - WANG Yu; WANG Yu; WU Na; YANG Lanqing (陆军军医大学学报)
Objective‍　‍To explore the association between the relative expression level of SNORD55 in peripheral blood and the outcomes of all-cause mortality and stroke in patients with atrial fibrillation （AF）， and to evaluate the predictive value of SNORD55 for prognosis. Methods‍　‍A total of 133 patients with non-valvular AF admitted in Department of Cardiology of the First Affiliated Hospital of Army Medical University from January 2014 to December 2017 were enrolled in this study. Their baseline information was collected， and the relative expression level of plasma SNORD55 was detected. Cox proportional hazards model was used to explore the association between the relative expression level of SNORD55 in peripheral blood and all-cause mortality as well as stroke in the patients. The predictive performance of CHA2DS2-VASc score for all-cause mortality and stroke was compared with the score combined with the relative expression level of SNORD55 in the AF patients. The area under the receiver operating characteristic curve （AUC） was utilized to evaluate the discrimination， and the net reclassification index （NRI） and comprehensive discriminant improvement index （IDI） were calculated to evaluate the improvement of reclassification ability. Decision curve analysis （DCA） was applied to analyze the change in clinical net benefit. Results‍　‍The results of multivariate Cox regression showed that high expression of SNORD55 in peripheral blood was an independent risk factor for all-cause mortality and stroke in the AF patients. In predicting the outcomes of all-cause mortality and stroke， the addition of relative expression SNORD55 level with the CHA2DS2-VASc score obtained higher AUC value ［0.80 （95%CI： 0.67~0.93） vs 0.67 （95%CI： 0.53~0.81）， P<0.05］. In predicting the outcome of all-cause death and stroke， combination of the relative expression level of SNORD55 with CHA2DS2-VASc score increased both NRI ［54.3 （95%CI： 10.6~61.9） vs 31.9 （95%CI： 2.8~47.5）， P<0.05］ and IDI ［16.1 （95%CI： 2.4~27.0） vs 7.9 （95%CI： 0.5~14.8）， P<0.05］. The results of DCA showed that our combination of CHA2DS2-VASc score relative expression level of SNORD55 had higher clinical net benefits than the foreign ABC score in the prediction of the outcomes. Conclusion‍　‍Peripheral blood SNORD55 level is an independent risk factor for all-cause mortality and stroke in AF patients， and has good predictive performance for all-cause mortality and stroke in the patients.